Contamination transport model by coupling analytic element and point collocation methods - Mohammadi, A.; Ghaeini-Hessaroeyeh, M.; Fadaei-Kermani, E. (Applied water science, 2020)
The prediction of contaminant transport in porous media is an important problem in order to prevent the pollution propagation in groundwater. The present model is developed by coupling two mesh-free approaches in order to overcome the restrictions of mesh-dependent methods. In this model, the ground water flow model is developed by analytic-element method and the contaminant transport model is developed by point collocation method in an unconfined aquifer. The model was developed and implemented by Python object-oriented programming language. A particle swarm optimization algorithm has been also utilized to calibrate the model. The model was applied for contamination transport in Astaneh-Kuchesfahan groundwater in north of Iran. Comparison of the model results with the observed data represents a reasonable agreement and capability of the present model in contaminant transport modeling. Moreover, the calculated value for coefficient of determination ( R 2 = 0.89) indicates that the calibrated parameters are acceptable.